2016
DOI: 10.3892/or.2016.4706
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tumor retention of radioiodinated anti-epidermal growth factor receptor antibody using novel bifunctional iodination linker for radioimmunotherapy

Abstract: Radioimmunotherapy (RIT) uses an antibody labeled with a radionuclide to deliver cytotoxic radiation to a target tumor cells. Radioiodine is most commonly employed to prepare radiolabeled proteins (antibodies, peptides) for in vitro and in vivo applications. A major shortcoming of radioiodinated proteins prepared by direct labeling methods is their deiodination in vivo. For the preparation of more stable radioiodinated antibodies, we developed a new linker (N-(4-isothiocyanatobenzyl)-2-(3-(tributylstannyl)phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A pre-requisite for successful use of molecular imaging is the development of a suitable probe that provides sufficiently high sensitivity and specificity. Anti-EGFR monoclonal antibodies labelled with several nuclides [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ] have been evaluated for EGFR visualization. Imaging sensitivity using monoclonal antibodies is, however, limited by their long blood residence and slow tumor accumulation thereby requiring several days (4–7 days) to obtain an acceptable imaging contrast in clinics [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A pre-requisite for successful use of molecular imaging is the development of a suitable probe that provides sufficiently high sensitivity and specificity. Anti-EGFR monoclonal antibodies labelled with several nuclides [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ] have been evaluated for EGFR visualization. Imaging sensitivity using monoclonal antibodies is, however, limited by their long blood residence and slow tumor accumulation thereby requiring several days (4–7 days) to obtain an acceptable imaging contrast in clinics [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…10-1550399KR]). Kim et al 47 showed that the tumor uptake value of [125I]I-IBPA-cetuximab was higher than that of [125I]I-cetuximab for up to 168 hours in athymic mice bearing human colorectal adenocarcinoma LS174T tumor xenografts (12.42 ± 1.63%ID/g vs 7.10 ± 1.54%ID/g at 48 hours after injection). The thyroidal uptake value of [125I]I-IBPA-cetuximab (0.09 ± 0.05%ID/g) after injection was ∌8-fold lower than that of [125I]I-cetuximab (0.69 ± 0.36%ID/g), with a statistically significant difference ( P < .005).…”
Section: Reviewmentioning
confidence: 99%
“…Unfortunately, when internalization occurs, intracellular catabolism of the antibody and dehalogenation result in the clearance of radioiodine from the target tissue, leading to signal loss and unspecific accumulation such as thyroid for iodine. A number of research groups have developed prosthetic or pendant groups to solve this problem [ 28 , 29 , 30 ], but they are still at the level of preclinical proofs of concepts. Concerning 18 F, although its ease of production in large quantities, its half-life and the low energy of the emitted positron make it an ideal versatile radionuclide for PET imaging, preparing 18 F-conjugates require time-consuming and challenging radiosynthesis.…”
Section: Labelling Techniquesmentioning
confidence: 99%